Picture books: an effective tool for disability education in preschools - Weiler, Megan, author; Bundy, Anita, committee member; Merz, Emily, committee member (Colorado State University. Libraries, 2025)
Picture books play a critical role in shaping a preschooler's beliefs on diversity and inclusion. Throughout history, popular picture books have lacked an accurate representation of disabilities. In the scenario where representation is included, the character commonly falls under the burden trope, the supercrip trope, and the medical model of disability. These tropes and stereotypes perpetuate ableism onto young readers. A lack of disability representation limits the confrontation of growing biases, allowing ableism to develop during a child's formative years. A picture book, Time to Fly! was constructed in order to combat this growing issue. This story included a character with a physical disability whose accomplishments were emphasized over their limitations. The character was also portrayed as a relatable individual to a preschool audience. Because of this positive and accurate representation, preschoolers without disabilities are able to empathize with the character and see them without the influence of ableism or unconscious biases. Additionally, preschoolers with a physical disability are able to grow their self-confidence. Seeing characters accomplish tasks with their disability lets the preschooler know that they are able to accomplish those tasks as well. The proposed methodology is structured as a pre-post pilot study, involving preschoolers aged five to six years old. A survey of questions asked to the preschoolers grants an evaluation of the picture book at the intended level. Edits to the picture book will be made after preschooler reactions are received, depending on the overall consensus behind Time to Fly!'s intended message. The work behind this project is intended to motivate educators to include books that contain disability representation and add the read-alongs into their preschool curriculum. Allowing these stories to hold a spot on a preschool shelf helps spread their message and promote inclusivity for all children. All children deserve to feel valued, represented, and understood.
Keywords: disability; preschool; literature; education; inclusion; representation